BUSINESS AND PUBLIC ADMINISTRATION: A STUDY OF PUBLIC-PRIVATE PARTNERSHIPS (PPPS) IN INDONESIAN INFRASTRUCTURE DEVELOPMENT - Erlita Khrisinta Dewi; Ahmed Al Fahad; Fatimah Al Rashid (Yayasan Adra Karima Hubbi, 2026)
Public-Private Partnerships (PPPs) have become an increasingly popular model for financing and developing infrastructure in many developing countries, including Indonesia. Given the significant infrastructure gaps in the country, particularly in transportation, energy, and urban development, PPPs offer a promising solution for mobilizing private investment and expertise while maintaining public accountability. This study investigates the role of PPPs in Indonesia’s infrastructure development, analyzing their effectiveness, challenges, and prospects for future growth. The research aims to assess how PPPs are implemented, their impact on project efficiency, and their contribution to Indonesia’s economic development. A qualitative research approach is used, employing case studies, interviews with key stakeholders, and a review of relevant policy documents. The findings reveal that while PPPs have contributed to accelerated infrastructure development, challenges such as regulatory inconsistencies, financial risks, and lack of transparency continue to hinder their success. However, with proper governance structures, risk-sharing mechanisms, and improved public-private collaboration, PPPs hold substantial potential for future infrastructure projects in Indonesia. The study concludes that PPPs, when effectively implemented, can significantly support sustainable development and economic growth in Indonesia.